The Main Directions of the Bank of Russia’s Activity in the System of Integrated Financial Regulation - Shaker, I.E.; Shaker, N.S. (Journal of Reviews on Global Economics, 2018)
Actuality: The transition to integrated financial regulation brought the issue on the central banks’ role in the new configuration of financial supervision; on the necessity of resistance to financial crises and systemic risks; on overcoming of sectoral fragmentation in the area of regulation and supervisory activities’ standardization based on best supervisory practices. Novelty: The regulatory and supervisory function has evolved into a critical factor in management of the financial system stability. Rethinking of the essence of the financial integral regulation has allowed distinguishing three separate directions: ensuring of financial stability, macroprudential oversight and regulation of moral hazard risk in the banking sector, financial institutions’ business behavior and limitation of the intention to establish the regulatory arbitrage. Practical Value: In countries, that have adopted the integral regulation of the financial market, in relation to all its sectors, the authors propose to develop and apply standards of the moral hazard risk regulation in the banking sphere and the business behavior of financial institutions; universal standards and technologies of regulation and supervision in order to limit the establishment of regulatory arbitrage; leveling of systemic risks of financially-credit sphere.